Metal-like texture design evaluation using sound symbolic words. Issue 3 (1st October 2016) - Sakamoto, Maki; Yoshino, Junya; Doizaki, Ryuichi; Haginoya, Masaharu
Abstract : Many products such as electronic appliances are made of imitation metals, which are lighter in weight and lower in cost than real metals. However, imitation metals sometimes look and feel cheap. This study proposes that differences in sound symbolic words associated with imitation and real metals can be used in metal texture design to make imitation materials look and feel like real materials. Japanese is known to have a large number of sound symbolic words, or "onomatopoeia, " for expressing textures. For example, onomatopoeia expressing a sense of smoothness often uses the consonant /s/ in the first syllable as in "sara-sara." We conducted psychological experiments where participants were asked to observe a pair of imitation and real materials without touching them and respond with onomatopoeic words that they felt were associated with them. Participants used significantly more onomatopoeic words for real materials than for imitation materials. Furthermore, we analyzed onomatopoeia obtained for both real metals and imitation metals using a system that quantifies the phonological information of onomatopoeia. The comparison of the onomatopoeia evoked by real metals and those evoked by imitation metals revealed differences in their texture feelings.